Development and characterization of novel microsatellite markers from the olive ridley sea turtle (Lepidochelys olivacea) - Aggarwal, Ramesh K.; Velavan, T. P.; Udaykumar, D.; Hendre, P. S.; Shanker, Kartik; Choudhury, B. C.; Singh, Lalji (Molecular ecology notes, 2004)
Olive ridley turtles, although widely distributed globally and in Indian coastal waters, have undergone declines in recent years due to anthropogenic factors, particularly fishery‐related mortality. Assessment of genetic variability in existing populations is critical to the development of effective conservation strategies. Here we describe the development of six highly polymorphic microsatellite loci from a simple sequence repeat‐enriched genomic DNA library of olive ridley turtle. Characterization of five of these loci using 83 individual olive ridley turtles revealed eight to 24 alleles per locus, high observed and expected heterozygosity values and broad cross‐species amplifications. The sixth microsatellite was found to be monomorphic in the olive ridley samples but was polymorphic in two related marine turtle species. These microsatellites thus provide efficient genetic markers to understand the population structure, phylogeography and species relationships of olive ridley and other marine turtle species.